Health promotion strategy for emergency choking at Elementary School Gisik Cemandi Sidoarjo - Ninik Ambar Sari; Sri Anik Rustini; Merina Widyastuti; Dwi Priyantini; Ceria Nurhayati (University of Merdeka Malang, 2023)
Choking is the entry of a foreign object into the throat or respiratory tract. This is a dangerous condition that can happen to anyone. In cases of choking in children, the initial treatment that can be done is back blows and chest thrusts. This activity was carried out to provide Health Education to students and teachers at SDN Gisik Cemandi Sidoarjo, as well as to gain skills in helping children and the community in their environment if a child experiences a choking incident. The implementation method is carried out in the form of a lecture using power points, posters with pictures of signs of choking, and how to handle it independently, and the Heimlich Maneuver. The results of the activity were that participants received information and increased their knowledge regarding the signs of choking, and how to handle it independently as well as the Heimlich Maneuver to students and teachers at SDN Gisik Cemandi Sidoarjo on November 11, 2023. The results of the socialization on handling emergency choking carried out at SDN Gisik Cemandi Sidoarjo were considered effective so that students and teachers are able to provide first aid in cases of choking.